New set-up for high-quality soft-X-ray absorption spectroscopy of large organic molecules in the gas phase - Holch, Florian; Huebner, Dominique; Fink, Rainer; Schoell, Achim; Umbach, Eberhard (Journal of Electron Spectroscopy and Related Phenomena, 2011)
We present a new experimental set-up for the investigation of large (>128 amu) organic molecules in the gas-phase by means of near-edge X-ray absorption fine structure spectroscopy in the soft X-ray range. Our approach uses a gas cell, which is sealed off against the surrounding vacuum and which can be heated above the sublimation temperature of the respective molecular compound. Using a confined volume rather than a molecular beam yields short acquisition times and intense signals due to the high molecular density, which can be tuned by the container temperature. In turn, the resulting spectra are of very high quality with respect to signal-to-noise ratio and energy resolution, which are the essential aspects for the analysis of fine spectroscopic details. Using the examples of ANQ, NTCDA, and PTCDA, specific challenges of gas phase measurements on large organic molecules with high sublimation temperatures are addressed in detail with respect to the presented set-up and possible ways to tackle them are outlined. © 2011 Published by Elsevier B.V. All rights reserved.